Role of MRI to Rule Out Non Discogenic Causes of Nerve Root Compression - Mian Waheed Ahmad, Nawaz Rashid, Saima Noreen, Kamran Sajjad Hashmi, Fareeha Nawaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose / intention of this study is to highlight that MRI is good diagnostic tool to interpret non discogenic causes of lumbosacral radiculopathy because of nerve root compression. Study Design: Cross-sectional descriptive study involving Medical Imaging (MRI) and clinical review. Place / Duration of the Study: This above mentioned study was piloted conducted in Diagnostic Radiology Wing of DHQ / Teaching Hospital, Gujranwala from 1st July 2017 till 30TH June 2018. Materials and Methods: 100 Patients with history of backache referred for MRI spine were scanned after informed consent atSiemens Syngo 1.5T MR system. Non-ionic Gadolinium contrast was used in suspected discospondylitis. Results: It was concluded from our study that lumbosacral ratio of nerve root compression due to non-discogenic causes (52%) (n=52) is greater than disc prolapse causes (48%) (n=48). Most common non discogenic cause of nerve root compression was facet joint hypertrophy. Other non discogenic causes of nerve root compression include traumatic (10%), Spondylolisthesis (5%), infection (14%), Neoplastic (2%) and sequestered disc segment (2%). Disc bulge was major discogenic cause of nerve root compression at lumbar spine. Conclusion: MRI provide valuable information regarding detection of lumbar radiculopathy causes. Most common causes of lumbar radiculopathy are non-discogenic pathologies rather discogenic cause.